Du Pont System Inside Measuring the Financial Performance of Food and Beverages Companies on the Indonesian Stock Exchange - Arini Lestari Aris; Valentino Aris; Siti Rahma Nurhaliza (CV. Sakura Digital Nusantara, 2023)
This study aims to find out Du Pont System in measuring the financial performance of Food and Beverages. The research sample is 18 Food and Beverages listed on the Indonesia Stock Exchange (IDX) in 2018-2020. Data collection is done by searching secondary data. Research results show the average change in NPM in the Food and Beverages industry in 2019 and 2020 is 1.52% and 0.8%. The average development of Total Assets Turn Over in the Food and Beverages industry in 2019 amounted to -0.03% and in 2020, it was 0.19%. And the company's financial performance based on the analysis of the Du Pont System method in the Food and Beverages industry in 2018-2020. Seen from the change in the average Return on Investment in 2019 of 1.59% and in 2020 by -3.91%. Rating The company's financial performance based on the analysis of the Du Pont System method in the Food and Beverages industry in 2012-2014. Judging from the value of Return on Investment PT. Multi Bintang Indonesia Tbk is ranked 1st in 2018-2019 with a Return On Investment value in 2018 of 42.39%, 2019 of 41.63%, and for 2020 rank 1 belongs to PT. Siantra Top Tbk with a Return On Investment value of 18.23%. Meanwhile PT. Sekar Bumi Tbk is ranked 18th with a Return on Investment value of 0.9% in 2018 and 0.05% in 2019. And in 2020 with a Return On Investment value of 0.31%.